GLOBAL ISSUES IN GENDER EQUALITY IN WORLD POLITICS - Kholboeva Zarifa Odil kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract There  are  several  issues  related  with  gender  equality  such  as  under representation of women in world politics, gender-based violence, economic inequality and  discriminatory  laws  and  policies.  Different  political  theories  see  these  issues differently, liberealistic feminism emphasizes individual rights while realistic feminism emphasizes security , power over social issues. Additionally, marxsim  links gender oppression to capitalist exploitation while post colonialism shows how imperialism have  shaped  gender roles.  Importantly,  radical feminism  highlights  patriachy  as  a biggest opposition towards gender equality.